2015
DOI: 10.1038/srep10196
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Plasmonic Enhanced Upconversion in Single NaYF4:Yb3+/Er3+ Nanocrystals

Abstract: By using silver nanoplatelets with a widely tunable localized surface plasmon resonance (LSPR), and their corresponding local field enhancement, here we show large manipulation of plasmonic enhanced upconversion in NaYF4:Yb3+/Er3+ nanocrystals at the single particle level. In particular, we show that when the plasmonic resonance of silver nanolplatelets is tuned to 656 nm, matching the emission wavelength, an upconversion enhancement factor ~5 is obtained. However, when the plasmonic resonance is tuned to 980 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 63 publications
1
27
0
Order By: Relevance
“…New upconverting nanoparticles with greater quantum yields are continually being synthesized [55] and some of these recent strategies could be utilized in this application. These techniques include plasmon-enhanced upconversion [56], dye sensitization antenna strategies [57], the use of different ceramic matrix materials [58], and the implementation of an undoped or "active" (Yb-containing) ceramic shell. [59][60][61] Although the need for good spectral overlap with the upconverter restricts the possible choices of oxygensensitive molecules, we can consider the use of molecules other than Ru(dpp)3Cl2.…”
Section: Discussionmentioning
confidence: 99%
“…New upconverting nanoparticles with greater quantum yields are continually being synthesized [55] and some of these recent strategies could be utilized in this application. These techniques include plasmon-enhanced upconversion [56], dye sensitization antenna strategies [57], the use of different ceramic matrix materials [58], and the implementation of an undoped or "active" (Yb-containing) ceramic shell. [59][60][61] Although the need for good spectral overlap with the upconverter restricts the possible choices of oxygensensitive molecules, we can consider the use of molecules other than Ru(dpp)3Cl2.…”
Section: Discussionmentioning
confidence: 99%
“…This process involves several energy transfers between the real electronic levels of the different ions. The main drawback is that the two photon absorption cross-section is weak [1][2][3] compared to organic molecules or inorganic quantum dots excited above their bandgap energy. In the case of RE-doped upconverting nanocrystals (UCN), one way to increase the efficiency is to couple them to metallic nanostructures that support a surface plasmon resonance (SPR).…”
Section: A Introductionmentioning
confidence: 99%
“…The recent trends in the field of lanthanide complexes are to introduce metal nanoparticles to tune its luminescent behavior and boost their efficiency for optical device applications. [11][12][13][14] Recently, Parola et al have given a detailed overview on different types of lanthanide based hybrid nanomaterials and demonstrated that, controlled coupling between plasmonics (attaching metal nanoparticles) and luminescence opens a wide field of intense research. 15 The luminescence mechanism of the lanthanide complexes are based on the ligand absorption coefficient and energy transfer to central metal ion (lanthanides).…”
Section: Introductionmentioning
confidence: 99%